A COMPARISON OF POST-OPERATIVE ANALGESIA WITH INTRAOPERATIVE PECTORAL NERVE BLOCK VERSUS CONVENTIONAL TECHNIQUE IN PATIENTS UNDERGOING MODIFIED RADICAL MASTECTOMY: A PROSPECTIVE, RANDOMIZED, AND DOUBLE-BLINDED STUDY - GAUTAM, ANKITA; KARAN, DAISY; BANERJEE, SWARNA; BISWAL, PRERNA; MODA, NUPUR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: We administered intraoperative pectoral nerve block after tissue resection was over and assessed its analgesic efficacy with conventional post-operative intravenous opioids in patients undergoing modified radical mastectomy. Methods: Sixty patients undergoing modified radical mastectomy surgery were enrolled in this prospective, randomized, and doubleblinded study. After general anesthesia and surgical resection in both groups, Group P received pectoralis (PECS) block under vision with ropivacaine at two points: 20 ml in the fascia over serratus anterior and 10 ml in the fascia between pectoral major and minor at the level of the third rib and Group T received tramadol (75 mg) in thrice daily frequency and 2% lignocaine infiltration at suture site. Primary objectives were to assess visual analog scale (VAS) scores over 24 h, time to first request for rescue analgesia (ketorolac) and total dose of analgesics needed, and secondary outcome was adverse effects and patient satisfaction score. “Mann–Whitney U test” and “Chi-square/Fischer exact test” were used for quantitative and categorical variables, respectively. Results: The mean time to the first rescue analgesia was 1175±120.21 and 1175±77.35 min and total analgesia requirement was equal (30.00±0.00 mg) in Group P and Group T, respectively. The mean VAS score over 24 h was comparable in both the groups. PECS block group had significantly less adverse effects and better satisfaction score. Conclusion: PECS block has similar analgesic efficacy as opioids but with better ability to mobilize the respective arm, better patient satisfaction score, and lesser adverse effects.